Monoclonal antibody‐mediated killing of tumour cells by neutrophils - Heemskerk, Niels (Eur J Clin Invest, 2018)
Neutrophils represent the most abundant population of circulating cytotoxic effector cells. Moreover, their number can be easily increased by treatment with granulocyte‐colony stimulating factor or granulocyte macrophage‐colony stimulating factor, without the need for ex vivo expansion. Because neutrophils express Fc receptors, they have the potential to act as effector cells during monoclonal antibody therapy of cancer. Additionally, as neutrophils play a role in the regulation of adaptive immune responses, exploiting neutrophils in mAb therapy may result in long‐term antitumour immunity. There is limited evidence that neutrophils play a prominent role in current immunoglobulin G‐based immunotherapy. However, as IgA induces neutrophil recruitment, novel therapeutic strategies that aim to target the IgA Fc receptor FcαRI may fully unleash the potential of enlisting neutrophils as cytotoxic effector cells in antibody therapy of cancer.